Language Innovation and Identity: The Sociolinguistics of Gen Z Slang on TikTok - Qotrunnada Shofiyah; Putri Nur Aulia; Euis Meinawati (LPPM Universitas Bumigora Mataram, 2026)
The rapid growth of social media has significantly influenced language use, particularly among Generation Z. One prominent linguistic phenomenon in digital communication is slang, which functions as a marker of identity, creativity, and social interaction. This study aims to analyze the use of slang by Generation Z on TikTok from a sociolinguistic perspective, focusing on forms, meanings, and contextual usage. This study employed a qualitative descriptive method to collect data from TikTok video captions and comment sections created by Generation Z users. The slang expressions were analyzed based on their linguistic characteristics, including semantic shift, code-switching, and lexical innovation, and were further interpreted using Halliday’s theory of register, which encompasses field, tenor, and mode. The findings indicate that semantic shift is the most dominant feature in Gen Z slang on TikTok, reflecting users’ creative reinterpretation of existing vocabulary. In addition, frequent code-switching between English and Indonesian highlights the influence of global digital culture on local language practices. Slang usage on TikTok is shaped by informal social relationships and multimodal communication, which encourage abbreviated forms and playful meaning construction. This study contributes to sociolinguistic research by providing insights into how slang functions in digital discourse and how Generation Z negotiates identity through language in social media environments, while also offering practical implications for educators and researchers seeking to understand contemporary youth language.